A wide range of benefits - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Henry Phombeya of Malawi?s Land Resource Centre outlines the benefits of various popular agroforestry species, including those offering soil fertility improvement.